Pengaruh Gaya Kepemimpinan, Budaya Organisasi, Dan Kepuasan Kerja Terhadap Perilaku Organizational Citizenship Behavior (OCB) Pada Para Guru Sekolah Terpadu Pahoa, Serpong - Alexander Widjanarko (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2020)
Organizational Citizenship Behavior (OCB) recently has been increasingly recognized its influence to the effectiveness of the organization. Because people in the organization work more than its duty, and contribute more than its expected. There are many factors affect the OCB. The objective of this study is to check the effect of leadership, organization culture, and job satisfaction to the OCB. This is an associative / relationship study, to find out the relationship between variables. Sampling technique of this study is Proportionate Stratified Random Sampling. From population of 264 teachers, 90 sample data was taken to be analyzed using multiple regression analysis. Result of the study found that simultaneously the leadership, organization culture, and job satisfaction give an influence of 39%. Whereas partially leadership has a low correlation, organization culture and job satisfaction have moderate correlation to OCB. Moreover these three variables have a positive and significant influence to the OCB. From questionaire analysis, it was found that leadership style is a team leader, organization culture is a mix between clan and hierarchy. Salary and management support are less satisfied compare others. For OCB, only aspect of sportsmanship reveal less strong.